Influence of variability in assessment of Breslow thickness, mitotic rate and ulceration among US pathologists interpreting invasive melanoma, for the purpose of AJCC staging. (29th May 2018) - Taylor, Laura; Hood, Kyle; Reisch, Lisa; Elmore, Joann; Piepkorn, Michael; Barnhill, Raymond; Knezevich, Stevan; Radick, Andrea; Elder, David
Abstract : Background: Melanoma staging has depended on depth of invasion (Breslow thickness, BT), mitotic rate (MR) and ulceration. In anticipation of the AJCC's eighth edition, variability in pathologists' assessment of these factors and consequently in tumor staging was assessed. Methods: One‐hundred and fifteen cases of invasive melanoma, established by a consensus panel, were assessed by 187 pathologists. Variation was studied in BT, the detection of mitotic figures, and ulceration. The sources of this variation and its effect on tumor staging are considered. Results: On average, participant assessments closely approached consensus BT. Greater variation was identified in the classification of mitogenicity, which (like ulceration) upstages a T1 melanoma from T1a to T1b in the seventh but not eighth edition. In cases with a T1a diagnosis by the consensus panel, 15.6% of participants identified one or more mitotic figures (indicative of a false positive); and in cases diagnosed asT1b by the consensus panel, 32.0% of participants failed to find mitotic figures (false negative). Conclusion: Variability in the staging of T1 melanoma among pathologists when using the AJCC seventh edition criteria is closely related to the detection of mitotic figures, with BT playing a less prominent role. Decreased variability is expected after implementation of the eighth edition.